Estudio e investigación de hongos en las aguas del Río Jubones en el sitio Ducos - Blacio Toro, Máximo E. (2006)
The work on the study and investigation of fungi in the waters of the Jubones River in the place Ducos was carried out during 5 weeks, taking 3 samples of waters every week in 3 points settled down in the methodology, with a temperature average of the water of 21,5 C and with a flow average of 60,18 m^3/seg. During the time of analysis we took a total 15 samples, which were taken to the laboratory of microbiology of the Faculty of Chemical Sciences at the University of Machala. Each one of the samples was grown in agar glucosado of Saboraud with their 3 respective repetitions.